Physician-patient boundaries in palliative care - Chong Yao Ho; Nicole-Ann Lim; Nur Diana Abdul Rahman; Min Chiam; Jamie Xuelian Zhou; Gillian Li Gek Phua; Eng Koon Ong; Crystal Lim; Anupama Roy Chowdhury; Lalit Kumar Radha Krishna (BMC Palliative Care, 2023)
Abstract Background Nurturing effective physician-patient relationships is essential to the provision of patient-centred care. Palliative care physicians may apply boundary-crossings or breaches in professional standards to nurture effective physician-patient relationships. Being highly individualized and shaped by the physician’s narratives, clinical experience, and contextual considerations, boundary-crossings are susceptible to ethical and professional violations. To better appreciate this concept, we employ the Ring Theory of Personhood (RToP) to map the effects of boundary-crossings on the physician’s belief systems. Methods As part of the Tool Design SEBA methodology, a Systematic Evidence-Based Approach (SEBA) guided systematic scoping review was employed to guide the design of a semi-structured interview questionnaire with palliative care physicians. The transcripts were simultaneously content and thematically analysed. The themes and categories identified were combined using the Jigsaw Perspective and the resulting domains formed the basis for the discussion. Results The domains identified from the 12 semi-structured interviews were catalysts and boundary-crossings. Boundary-crossings attempt to address threats to a physician’s belief systems (catalysts) and are highly individualized. Employ of boundary-crossings depend on the physician’s sensitivity to these ‘catalysts’, their judgement and willingness to act, and their ability to balance various considerations and reflect on their actions and their ramifications. These experiences reshape belief systems, understandings of boundary-crossings and may influence decision-making and practice, underscoring the potential for greater professional breaches when unchecked. Conclusion Underlining its longitudinal effects, the Krishna Model underscores the importance of longitudinal support, assessment and oversight of palliative care physicians, and lays the foundation for a RToP-based tool to be employed within portfolios.